2020
DOI: 10.3390/ani10122412
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the COVID-19 Pandemic on Riding Lesson Barns and Summer Camps in Ontario

Abstract: The COVID-19 pandemic has direct effects on the operations of riding lesson facilities and summer camps, with little government guidance on how to implement these. An online survey link was distributed to riding lesson facilities in Ontario. Descriptive statistics of respondents (n = 72) reported a decrease in both the number of riding lessons offered and the number of riding students per lesson. Scheduling riding times and limiting access to specific places on the farm ensured controlled access to the farms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…A minority of respondents reported that due to lockdown and being furloughed from work, they were able to spend more time with their horse, a benefit also noted by Merkies et al in their Ontario-based study [ 13 ]. The emotional support provided by equines is likely underestimated in comparison to other companion animal species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A minority of respondents reported that due to lockdown and being furloughed from work, they were able to spend more time with their horse, a benefit also noted by Merkies et al in their Ontario-based study [ 13 ]. The emotional support provided by equines is likely underestimated in comparison to other companion animal species.…”
Section: Discussionmentioning
confidence: 99%
“…The rigor of these measures differed between respondent reports from simply abiding by social distancing regulations while on the yard, to disinfecting all surfaces touched, using disposable gloves, and ensuring that the respondent was the only person touching their horse and all their associated equipment. These measures closely resemble those used in equine establishments in Ontario [ 13 ]. Facemasks were not reported by respondents as one of the biosecurity measures they used while with their horses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential changes in horse owner perception following pandemic-associated isolation were explored by Hockenhull and Furtado [ 40 ], who suggested that the pandemic may have offered equestrian stakeholders an opportunity for reflection upon how they derived their satisfaction from involvement with horses. Equestrians deriving pleasure from undertaking tasks other than riding, such as grooming and general horse care, could be a positive outcome of the pandemic that others have also noted [ 41 ], and this phenomenon may have positive impacts on owners’ relationships with their animals in the future.…”
Section: Discussionmentioning
confidence: 99%